Risk Factors Of Job-Related Depression In Laboratory Technicians In Hospital Universiti Sains Malaysia (HUSM) And Kementerian Kesihatan Malaysia (KKM) Hospitals In Kelantan. - Aziah, BD; Rusli, BN; Winn, T; Naing, L; Tengku, MA (2004)
Across-sectional study was conducted to determine the risk factors of job-related depression in laboratory technicians in Hospital Universiti Sains Malaysia (HUSM) and Kementerian Kesihatan Malaysia(KKM) Hospitals in Kelantan, between September 2001 and February 2002.